(3GdeZQH aj Mdi GdeZQHs - (3Ydj Hf ehSi Hf eMeO Hf YHO Gdedc GHf SYjO, GdYfSj GdeOdLj GdeZQHj , CHh GdMSf, fhQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg agPG GdcJGH GdKGfi ef GdcJH GdPj jTJed YdjgG cJGH edcI JOejQ, hgh cJGH GdESJYGfI ai Mdi bQjI efJGfI s
(3BNQgG (B:s
(3hHgG ced LejY cJGH GdeZQH Mdi GdeZQH hPdc HNW eced JUfjag Ydi Hf SYjO ai eOjfI MdH HJGQjN SfI SHY hGQHYjf hSJeGFI s
(3HChdgG agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B249s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B337 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B576 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B408 s
Keywords: (3GdJGQjNs